Student’s environmental literacy based on Adiwiyata and non-Adiwiyata at senior high school in Sleman, Yogyakarta - Dwi Astuti; Tien Aminatun (University of Muhammadiyah Malang, 2020)
Environmental problems in Indonesia increase the government's efforts in shaping students' environmental care character through the Adiwiyata program. This study was conducted to determine differences in environmental literacy between Adiwiyata and non-Adiwiyata schools in Senior High School (SHS) in Sleman Regency, Yogyakarta. This survey research using a conventional sampling technique. The sample involved in this study was 1,568 students from nine schools in Sleman Regency. The data collection instrument refers to the instrument developed by the North American Association for Environmental Literacy (NAAEE) and is supported by interviews and observations. Measurement of environmental literacy in this study was carried out in two domains: competence and disposition. Comparative data analysis used the Mann Whitney test assisted by SPSS 25 for windows. The results showed that students' environmental literacy in the Sleman Regency was included in the good category in the competency and disposition domain. Environmental literacy abilities in Adiwiyata and non-Adiwiyata schools differ, both in the competency domain which includes competence (sig <0.05) and environmental literacy (sig 0.002), and in the disposition domain with sig <0.05. These results concluded that there were differences in students' environmental literacy skills between Adiwiyata and non-Adiwiyata schools. This research recommends that schools initiate programs to strengthen environmental literacy through strengthening the character of caring for the environment.